Toradora!. Volume 7 - Takemiya, Yuyuko, 1978- (Seven Seas Entertainment, 2019)
The festive season brings good cheer<U+2013>and new trouble! Taiga<U+2019>s back from suspension and suddenly on her best behaviour, Minori<U+2019>s struggling with softball club and being weird around Ryuuji, and Kitamura, newly christened as a student council president, is planning a Christmas party! With preparations for the celebration going full-steam under these volatile conditions, it looks like stocking stuffers won<U+2019>t be the only surprise in wait before the year is over!